Cell Analysis from Dried Blood Spots: New Opportunities in Immunology, Hematology, and Infectious Diseases. Issue 18 (18th July 2021) - Ait Belkacem, Ines; Mossadegh‐keller, Noushine; Bourgoin, Penelope; Arnoux, Isabelle; Loosveld, Marie; Morange, Pierre‐emmanuel; Markarian, Thibaut; Michelet, Pierre; Busnel, Jean Marc; Roulland, Sandrine; Galland, Franck; Malergue, Fabrice
Abstract: Blood cell analysis is a major pillar of biomedical research and healthcare. These analyses are performed in central laboratories. Rapid shipment from collection site to the central laboratories is currently needed because cells and biomarkers degrade rapidly. The dried blood spot from a fingerstick allows the preservation of cellular molecules for months but entire cells are never recovered. Here leucocyte elution is optimized from dried blood spots. Flow cytometry and mRNA expression profiling are used to analyze the recovered cells. 50–70% of the leucocytes that are dried on a polyester solid support via elution after shaking the support with buffer are recovered. While red blood cells lyse upon drying, it is found that the majority of leucocytes are preserved. Leucocytes have an altered structure that is improved by adding fixative in the elution buffer. Leucocytes are permeabilized, allowing an easy staining of all cellular compartments. Common immunophenotyping and mRNAs are preserved. The ability of a new biomarker (CD169) to discriminate between patients with and without Severe Acute Respiratory Syndrome induced by Coronavirus 2 (SARS‐CoV‐2) infections is also preserved. Leucocytes from blood can be dried, shipped, and/or stored for at least 1 month, then recovered for a wide variety of analyses, potentially facilitating biomedical applications worldwide. Abstract : A new method is described in which blood is dried on a polyester solid support, shipped, and/or stored at room temperature for at least 1 month. Leucocytes are recovered for a wide variety of biomedical analyses. The method has significant implications for resource limited settings and may facilitate patient management worldwide.